2019
DOI: 10.1177/1558944718825137
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Courses of the Palmar Cutaneous Branch of the Median Nerve in Relation to the Flexor Carpi Radialis Tendon for ORIF of Distal Radius Fractures

Abstract: Background: The purpose of this study was to prospectively document the incidence of variations in the course of palmar cutaneous branch of the median nerve (PCBMN) that may increase the risk of injury to the nerve during the flexor carpi radialis (FCR) approach. We hypothesize that the incidence of anomalous branching of the PCBMN around the FCR sheath will be approximately 5%. Methods: All cases that met inclusion criteria between November 2013 and March 2018 were included. The operating surgeon made the fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
16

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 39 publications
(53 reference statements)
0
3
0
16
Order By: Relevance
“…Al respecto, se han realizado algunos estudios cadavéricos basados en la concepción de que la comprensión profunda de la anatomía disminuye la posible lesión iatrogénica. 7,14,19 Según la encuesta, se encontraron algunas discrepancias entre los cirujanos que operaron estas fracturas. No obstante, hubo una tendencia a abrir el tendón FCR, y esto no fue diferente entre los cirujanos ortopédicos generales o de mano.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Al respecto, se han realizado algunos estudios cadavéricos basados en la concepción de que la comprensión profunda de la anatomía disminuye la posible lesión iatrogénica. 7,14,19 Según la encuesta, se encontraron algunas discrepancias entre los cirujanos que operaron estas fracturas. No obstante, hubo una tendencia a abrir el tendón FCR, y esto no fue diferente entre los cirujanos ortopédicos generales o de mano.…”
Section: Discussionunclassified
“…Todos ellos abren la vaina FCR y consideraron este abordaje como más seguro en este sentido, al contrario de lo que han planteado algunos estudios anatómicos y observacionales. 7,19,20 Un estudio anatómico realizado por Conti Mica et al (2016) 7 sobre abordajes de radio distal volar demostró que al abrir el lado cubital del FCR en el abordaje de Henry modificado (que se realiza abriendo la vaina del FCR), tanto la RCP como la mediana los nervios están en peligro. No obstante, la arteria radial está más cerca y por tanto más susceptible de lesionarse en el abordaje clásico de Henry (2).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…The palmar cutaneous branch of the median nerve is within the surgical field during the FCR approach, and variations in its course can predispose it to iatrogenic injury. Glickel et al 17 found that the nerve crosses or is inside the FCR sheath in 18.8% of their 101 patient series. The nerve can also be injured if the palmaris longus (PL) was confused for the FCR on palpation and the approach, which results in dissection in the interval between the PL and FCR-where the branch is most often found.…”
Section: Palmar Cutaneous Branch Of the Median Nervementioning
confidence: 95%